PLAN ESTRATEGICO APREPROSA – POTENCIAR CAPACIDADES PRODUCTIVAS PARA REVERTIR CRISIS ALIMENTARIA - Godoy, Antonia; Martinez, Mirta C.; Franco, Mauricio J.; Krieger, Alejandra C. (Salão do Conhecimento, 2013)
Resumo